Respuesta :
5^(x+7)=(1/625)^(2x-13)
We move all terms to the left:
5^(x+7)-((1/625)^(2x-13))=0
Domain of the equation: 625)^(2x-13))!=0
x∈R
We add all the numbers together, and all the variables
5^(x+7)-((+1/625)^(2x-13))=0
We multiply all the terms by the denominator
(5^(x+7))*625)^(2x+1-13))-((=0
We add all the numbers together, and all the variables
(5^(x+7))*625)^(2x-12))-((=0
We add all the numbers together, and all the variables
(5^(x+7))*625)^(2x=0
not sure if this is right :/
Hey there! the answer to this equation is
x=1/3125
Explanation
You move all the terms to the left:
5^x-(1/625)^(2x-13)=0
Then add all the numbers altogether, and the variables too
5^x-(+1/625)^(2x-13)=0
Now get rid of the parentheses
5^x-1/625^2x-13=0
Multiply all of them by the denominator
5^x*625-1 .2x-13=0
Finally , move all terms to the left, and all other terms to the right
This should be your final answer
3125x=1
Hope this helped you and if im wrong, correct me.